2012
DOI: 10.2172/1057209
|View full text |Cite
|
Sign up to set email alerts
|

MPACT Fast Neutron Multiplicity System Design Concepts

Abstract: This report documents work performed by Idaho National Laboratory and the University of Michigan in fiscal year (FY) 2012 to examine design parameters related to the use of fast-neutron multiplicity counting for assaying plutonium for materials protection, accountancy, and control purposes. This project seeks to develop a new type of neutron-measurement-based plutonium assay instrument suited for assaying advanced fuel cycle materials. Some current-concept advanced fuels contain high concentrations of plutoniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The idea for using the time-correlation for non-destructive inspection of objects containing fissile material has been pursued for "passive" interrogation schemes [21,22,24,[26][27][28][29][30][49][50][51][52] (where the natural background initiates the fission chains) and for "active" interrogation schemes [19,20,23,25,53] (where a beam of particles induces the fission chains).…”
Section: Time-correlation Of Fission-chain Neutronsmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea for using the time-correlation for non-destructive inspection of objects containing fissile material has been pursued for "passive" interrogation schemes [21,22,24,[26][27][28][29][30][49][50][51][52] (where the natural background initiates the fission chains) and for "active" interrogation schemes [19,20,23,25,53] (where a beam of particles induces the fission chains).…”
Section: Time-correlation Of Fission-chain Neutronsmentioning
confidence: 99%
“…All of these methods use single-particle signals. Multi-particle schemes, usually two-and three-neutron signals have also been pursued, with photon [19,20] and neutron [21][22][23][24][25] beams as well as in passive interrogation [26][27][28][29][30][31][32], where ambient radiations are used to induce the signals. Here we report on an active interrogation method using 9 MeV Bremsstrahlung photons to induce the emission of time-correlated, prompt neutrons measured within the Prompt Neutrons from Photofission (PNPF) system developed at Passport Systems Inc. (PSI) [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…PuFirst order factor of spontaneous fission; vsf,2-240 Pu Second order factorial moments of spontaneous fission; vsf,3-240 Pu Third order factorial moments of spontaneous fission; vi1-239 Pu The First Order Factor of Induced Fission; vi2-239 Pu the second order factor of the fission multiplicity; vi3-239 Pu triggering the third order factor of fission multiplicity; fddouble counting rate (Doubles) gate width factor; ft-triple count factor (Triples) of the door width factor; scattering crosstalk rate; ε-detection efficiency. After solving M, the values of F and α are solved by the equation 5and (6)…”
Section: Quantum Description Of Fast Neutron Multiplicitymentioning
confidence: 99%
“…In order to maintain good detection efficiency, only through quantitative simulation to get accurate results. The model of the measurement device used in the simulation study (the scintillator position shown in Fig.3) was established by reference to the model in reference [6]. The geometric layout of the measuring device is a 3×8, uniformly wound ∅5 "x 2" BC-501-A liquid scintillator detector with a detector surface distance of 20 cm from the center axis.…”
Section: Simulation Studymentioning
confidence: 99%
“…[3,4,5] This work, supported by the U.S. Department of Energy's Fuel Cycle Research and Development program and its Materials Protection, Accounting, and Control Technologies (MPACT) program, has been a collaborative effort including staff at INL as well as staff and students in the Department of Nuclear Engineering & Radiological Sciences at the University of Michigan (UM). These activities have included simulation and modeling using the MCNPX-PoliMi Monte Carlo simulation tool and experiments to validate the simulations, development of hands-on experimental methods, and the discovery of pitfalls and challenges in performing these types of measurements that cannot be identified any other way.…”
Section: Introductionmentioning
confidence: 99%